Online Learning Design for Animalia Classification Materials With Discovery Learning-Based Learning Videos and Vee . Diagrams - Harendra, Astried Pascafitri; Karyanto, Puguh; Muzzazinah, Muzzazinah (Bioedukasi: Jurnal Pendidikan Biologi, 2021)
Preliminary study was done by giving a cognitive test using a two-tier diagnostic test to 147 students of 10 high schools from 5 districts. It showed that the questions that a respondent can accomplished was only 56%. This research aims to 1) know the characteristics of online learning using video for animalia classification materials based on discovery learning and vee diagrams 2) determine the feasibility of learning videos for animal classification based on discovery learning and Vee diagrams. This research is a qualitative descriptive research. The research subjects were biology teachers and grade X students of public senior high school in Wonogiri. The respondents were purposively selected. Data was collected from observation, interview, and documentation. Data collection instrument were questionnaire for teachers on learning models and animal classification materials, students' questionnaires on learning video. The findings are 1) The video for animalia classification made the learning more interesting, help the students to build concepts and make learning more meaningful 2) learning video is suitable for use in online learning animal classification based on the results of teacher questionnaires at four aspects: (1) selection of learning resources and media teaching 87,50% (2) learning approaches and methods 87,50% (3) learning model syntax 90,63% (4) Evaluation 83,3% and the average result for material content 91,11%. Students also gave positive responses on learning video: (1) display 82,47% (2) materials 81,24% (3) learning model 81,9%.